2010
DOI: 10.1271/bbb.90805
|View full text |Cite
|
Sign up to set email alerts
|

New Syntheses of 1,7-Dimethylnonyl Propanoate, the Western Corn Rootworm Pheromone, in Four Different WaysviaCross Metathesis, Alkylation and Coupling Reactions

Abstract: A mixture of the four stereoisomers of 1,7-dimethylnonyl propanoate, the female sex pheromone of the western corn rootworm (Diabrotica virgifera virgifera LeConte), was synthesized in four different ways by employing one of the following four reactions as the key step: (i) cross metathesis using the Grubbs I catalyst, (ii) cross metathesis using the Grubbs II catalyst, (iii) alkylation of an alkynide anion, and (iv) Grignard coupling in the presence of dilithium tetrachlorocuprate. Although the cross metathesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Addition of vinylmagnesium bromide ( 2 ) to 4 gave 5 , which was treated with 47% hydrobromic acid to furnish allylic bromide 6 . Alkylation of methyl acetoacetate ( 3 ) with 6 in the presence of potassium carbonate in acetone and DMF 27 ) afforded 7 , whose alkaline hydrolysis and decarboxylation gave unsaturated ketone 8 as an ( E , Z )-mixture. Then the same sequence of vinylation/hydrobromic acid treatment/acetoacetic ester synthesis was repeated to give 12 via 9 , 10 and 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Addition of vinylmagnesium bromide ( 2 ) to 4 gave 5 , which was treated with 47% hydrobromic acid to furnish allylic bromide 6 . Alkylation of methyl acetoacetate ( 3 ) with 6 in the presence of potassium carbonate in acetone and DMF 27 ) afforded 7 , whose alkaline hydrolysis and decarboxylation gave unsaturated ketone 8 as an ( E , Z )-mixture. Then the same sequence of vinylation/hydrobromic acid treatment/acetoacetic ester synthesis was repeated to give 12 via 9 , 10 and 11 .…”
Section: Resultsmentioning
confidence: 99%
“…They are species-specific and non-toxic, and the risk of pests evolving resistance to their own pheromone is very low. Compared to current standard approaches to pheromone synthesis [ 3 ], the use of biological factories for pheromone production may have several advantages, allowing cost-efficient production of moderate to large quantities of pheromones with high purity and a minimum of waste. A series of proof-of-concept studies have clearly demonstrated the potential of producing moth pheromones in both plant and yeast factories [ 4 7 ] to replace conventionally produced pheromones in existing systems for pheromone-based pest control.…”
Section: Introductionmentioning
confidence: 99%
“…They are species-specific and nontoxic, and the risk of pests evolving resistance to their own pheromone is very low. Compared to current standard approaches to pheromone synthesis (Mori 2010), the use of biological factories for pheromone productions may have several advantages, allowing cost-efficient production of moderate to large quantities of pheromones with high purity and a minimum of waste. A series of proof-of-concept studies have clearly demonstrated the potential of producing moth pheromones in both plant and yeast factories (Hagström et al 2013b;Ding et al 2014;Xia et al 2020;Holkenbrink et al 2020) to replace conventionally produced pheromones in existing systems for pheromone-based pest control.…”
Section: Introductionmentioning
confidence: 99%